Aberrant right subclavian artery in video-assisted thoracoscopic esophagectomy - Lin, Yidan (Pioneer Bioscience Publishing Company, 2013)
When performing video-assisted thoracoscopic esophagectomy, the area at the level above the aortic and in the space between the esophagus and the spine, is usually regarded as a safe area for dissection of upper segment of thoracic esophagus. However, an aberrant right subclavian artery may appear in this area and lead to disastrous complications. We reported a case of aberrant artery encountered during video-assisted thoracoscopic esophagectomy. In order to avoid iatrogenic damage to this artery, it was converted to thoracotomy.